2018
DOI: 10.30877/ijmh.5.4.2018.412-418
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Depressive Features and Perceived Social Support in patients with Miscarriage

Abstract: Background: In developing world, the number of women undergoing miscarriage has increased. Women facing miscarriage are susceptible to develop depression and the risk is more if the perceived social support is low or not adequate. This study was conducted to assess the presence of depressive features and perceived social support and to correlate between the two entities in patients with miscarriage. Methods: This was a cross-sectional, single interview study conducted in 100 consecutive patients with miscarria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…27 In women with psychological problems such as anxiety and depression, the perceived social support level decreases and thus they become more hopeless. 28,29 Similarly, in the present study, in both groups, hopelessness levels increased and perceived social support levels decreased as depression and anxiety levels increased. In a study conducted by Zu et al, it was found that depressive symptoms were 2.7 times more in women with TM and 48.8% of women with TM were at high risk for anxiety.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…27 In women with psychological problems such as anxiety and depression, the perceived social support level decreases and thus they become more hopeless. 28,29 Similarly, in the present study, in both groups, hopelessness levels increased and perceived social support levels decreased as depression and anxiety levels increased. In a study conducted by Zu et al, it was found that depressive symptoms were 2.7 times more in women with TM and 48.8% of women with TM were at high risk for anxiety.…”
Section: Discussionsupporting
confidence: 77%
“…Social support is very important for pregnant women who are at risk of abortion to cope effectively with this stress. 29 The mean MSPSS scores the participants with TM were lower than those of the participants without TM. Social support gives people a sense of being loved and cared, and provides a respectable and moral bond between people.…”
Section: Discussionmentioning
confidence: 88%
“…Social support not only helps individuals to accept and confront the situation they are in but also allows them to receive help from others, especially in difficult times. For this reason, having social support is very important for pregnant women with TM so that they can cope effectively with the stress they are experiencing 11 . In our study, it was determined that the level of perceived social support was lower in women with TM compared to those without TM, and that as the level of perceived social support increased, anxiety, depression, and hopelessness scores decreased.…”
Section: Discussionmentioning
confidence: 79%
“…Social support, including spousal support, is a protective factor against mental health issues such as antenatal anxiety, depression, and hopelessness in pregnant women with TM 9 . However, high levels of anxiety, depression, and hopelessness in women who are at risk of abortion during pregnancy may also reduce their perceived social support 10,11 . Strong perceived social support is important in reducing and preventing these problems 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation